Does Shari’ah Screening Cause Abnormal Returns? Empirical Evidence from Islamic Equity Indices - Ashraf, Dawood (Journal of business ethics, 2016)
Islamic equity funds are subject to the screening criteria for stock selection imposed by the principles of Islamic jurisprudence (Shari’ah). Equities must pass three basic screens: revenue source, business activity, and financial factors to be included in an Islamic fund. However, screening criteria are not universal especially for the financial factors. One can use financial ratios based on either the book-value of total assets or the market-value of equity for screening of stocks. This may not only result in a different portfolio composition but also entail diverse rebalancing and monitoring costs. The performance of 29 Islamic equity indices (IEIs) versus conventional indices from four major international index providers using different Shari’ah screening criteria are analyzed in a single as well as in a multi-equation framework. The use of a multi-equation framework has the added advantage of utilizing the information content of different screening criteria adopted by different index providers. The empirical findings suggest that the difference in screening criteria does not significantly affect the performance of IEIs. Returns deviation, if any, stems from the relative riskiness of the IEI as compared with the relevant benchmark. Work needs to done to streamline the quantitative screening criteria to avoid confusion among the investing public.